2017
DOI: 10.1039/c7tb01538k
|View full text |Cite
|
Sign up to set email alerts
|

Protein–polysaccharide complexes for enhanced protein delivery in hyaluronic acid templated calcium carbonate microparticles

Abstract: International audienceThe controlled delivery of proteins within calcium carbonate (CaCO 3) particles is currently widely investigated. The success of these carriers is driven by ionic interactions between the encapsulated proteins and the particles. This poses a great limitation on the successful loading of proteins that have no ionic affinity to CaCO 3. In this study, we explored the use of polysaccharide–protein interactions to strongly enhance the encapsulation of proteins in CaCO 3 microparticles. Previou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 45 publications
0
14
0
Order By: Relevance
“…6 Subsequently, it was shown that aragonite is bioresorbable and that aragonite and other calcium carbonate polymorphs can serve as a drug release system. [7][8][9][10][11][12][13] Despite the widespread occurrence of calcium carbonate in the biosphere, e.g., in human otoliths, it seems that the full potential of the calcium carbonate system is not yet tapped for the purposeful design of bioactive and bioresorbable biomaterials/ bioceramics. Recent research also rose our awareness that calcium carbonate formation contributes to the bioactivity of bioglass.…”
Section: Introductionmentioning
confidence: 99%
“…6 Subsequently, it was shown that aragonite is bioresorbable and that aragonite and other calcium carbonate polymorphs can serve as a drug release system. [7][8][9][10][11][12][13] Despite the widespread occurrence of calcium carbonate in the biosphere, e.g., in human otoliths, it seems that the full potential of the calcium carbonate system is not yet tapped for the purposeful design of bioactive and bioresorbable biomaterials/ bioceramics. Recent research also rose our awareness that calcium carbonate formation contributes to the bioactivity of bioglass.…”
Section: Introductionmentioning
confidence: 99%
“…The high protein entrapment efficiency of CaCO 3 particles was reported in [ 130 ]. The interactions of proteins with CaCO 3 particles were investigated [ 131 ] and used for the development of HYH-based composites containing CaCO 3 particles loaded with proteins for controlled protein release.…”
Section: Hyh–bioceramic and Hyh–bioglass Compositesmentioning
confidence: 99%
“…Aft er dissolution of CaCO 3 cores in the presence of chelate compounds (e.g., ethylenediaminetetraacetic acid), these multilayered shells were used as capsules for delivery of biologically active compounds [2]. In some cases, carbonate cores were not dissolved, but used together with their PE shells [3][4][5]. Since one of the objectives of employing delivery systems is to provide prolonged release of an encapsulated MC, preservation of the porous core increases resistance of the structure against external infl uence and thus helps attain this goal.…”
Section: Introductionmentioning
confidence: 99%